2022
DOI: 10.1177/15910199221111284
|View full text |Cite
|
Sign up to set email alerts
|

Retreatment of previously flow diverted intracranial aneurysms with the pipeline embolization device

Abstract: Background and Purpose Flow diversion of intracranial aneurysms with the Pipeline Embolization Device (PED) is frequently performed, but the outcomes of retreatment for aneurysms that failed to occlude after prior treatment with PED have not been well studied. Here, we report the safety and efficacy of PED retreatment after initial failure to occlude. Materials and Methods Clinical and angiographic data from eligible patients were retrospectively assessed for demographics, aneurysm occlusion status, and clinic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 26 publications
0
1
0
Order By: Relevance
“…26 Our results are more similar to another study of 42 patients (median aneurysm size 13 mm) by Lauzier et al, which demonstrated that repeat flow diversion of intracranial aneurysms was associated with a 26% rate of complete occlusion and only a 45% rate of improved aneurysmal filling at 14 months median followup. 27 The highest-quality evidence on this topic comes from a retrospective multicenter review of 95 patients (median aneurysm size 9 mm) by Salem et al, which demonstrated a 67% complete or near-complete occlusion rate after two-stage flow diversion. 28 In contrast to all previous studies, our study was focused on patients with large aneurysms (>10 mm) and demonstrates a 50% near-complete occlusion (OKM C) and 0% complete occlusion (OKM D).…”
Section: Generalizabilitymentioning
confidence: 99%
“…26 Our results are more similar to another study of 42 patients (median aneurysm size 13 mm) by Lauzier et al, which demonstrated that repeat flow diversion of intracranial aneurysms was associated with a 26% rate of complete occlusion and only a 45% rate of improved aneurysmal filling at 14 months median followup. 27 The highest-quality evidence on this topic comes from a retrospective multicenter review of 95 patients (median aneurysm size 9 mm) by Salem et al, which demonstrated a 67% complete or near-complete occlusion rate after two-stage flow diversion. 28 In contrast to all previous studies, our study was focused on patients with large aneurysms (>10 mm) and demonstrates a 50% near-complete occlusion (OKM C) and 0% complete occlusion (OKM D).…”
Section: Generalizabilitymentioning
confidence: 99%